Phospholamban: a tiny protein with a prominent role in the regulation of cardiac relaxation and contractility - Mattiazzi, Alicia Ramona (2010)
Phospholamban (PLN) is a small sarcoplasmic reticulum (SR) protein that in the dephosphorylated state tonically inhibits the SR Ca2+-ATPase (SERCA2a). Different type of evidence to be described, points to PLN as a crucial regulator of basal cardiac Ca2+ cycling, contractility and relaxation and as a main determinant of β -adrenergic stimulatory responses in vivo. The involvement of PLN and PLN phosphorylation under pathological conditions will be also discussed.